2
$\begingroup$

$$a_n=\frac{1}{\pi}\left[\int_{-\pi}^{-\frac{\pi}{2}}(\sin 2x)(\cos nx)dx+\int_{0}^{\pi}(\sin 2x)(\cos nx)dx\right];\ldots (A)$$

The answer is

$$\frac{-2}{\pi}\frac{1+\cos(\frac{n\pi}{2})}{n^2-4}.$$

My attempt:

$\int(\sin 2x)(\cos nx)dx$

$=\frac{1}{2}\int[\sin(n+2)x-\sin(n-2)x]dx$

$=\frac{1}{2(n-2)}\cos(n-2)x-\frac{1}{2(n+2)}\cos(n+2)x$

S0,

$\int_{-\pi}^{-\frac{\pi}{2}}(\sin 2x)(\cos nx)dx$ $=\frac{1}{2(n-2)}\cos(n-2)(\frac{\pi}{2})-\frac{1}{2(n+2)}\cos(n+2)(\frac{\pi}{2})-\frac{1}{2(n-2)}\cos(n-2)(\pi)+\frac{1}{2(n+2)}\cos(n+2)(\pi)$

And

$\int_{0}^{\pi}(\sin 2x)(\cos nx)dx$ $=\frac{1}{2(n-2)}\cos(n-2)(\pi)-\frac{1}{2(n+2)}\cos(n+2)(\pi)-\frac{1}{2(n-2)}+\frac{1}{2(n+2)}$

form equation $(A)$,

$a_n=\frac{1}{\pi}[\frac{1}{2(n-2)}\cos(n-2)(\frac{\pi}{2})-\frac{1}{2(n+2)}\cos(n+2)(\frac{\pi}{2})-\frac{1}{2(n-2)}+\frac{1}{2(n+2)}]$

$\Rightarrow a_n=\frac{1}{\pi}[\frac{(n+2)\cos(n-2)(\frac{\pi}{2})-(n-2)\cos(n+2)(\frac{\pi}{2})-4}{2(n-2)(n+2)}]$

I couldn't come up with the result $\frac{-2}{\pi}\frac{1+\cos(\frac{n\pi}{2})}{n^2-4}$.

$\endgroup$
2
$\begingroup$

$\cos{a-b}=\cos a \cos b + \sin a \sin b$
$\cos{\frac{(n-2)\pi}2}=-\cos{\frac{n\pi}2}$ since $\sin \pi=0$ and $\cos \pi=-1$
$(n-2)(n+2)=n^2-4$.

Your answer should simplify to the required answer.

$\endgroup$
  • $\begingroup$ $\cos\frac{(n-2)\pi}{2}=\cos[\frac{n\pi}{2}-\pi]=-\cos\frac{n\pi}{2}$. But if $n$ is odd integer, doesn't $\cos$ changes to $\sin$? $\endgroup$ – ABC Jul 26 '13 at 10:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.